FOLLICULAR DYNAMICS DURING ESTROUS CYCLE IN POSTPUBERTAL AND POSTPARTUM GIR CATTLE - Hadiya, KK; DHAMI, A J; PATEL, J A; LUNAGARIYA, P M (The Indian Journal of Animal Reproduction, 2022)
The follicular dynamics of an entire estrous cycle was monitored daily between two consecutive estruses in 6 postpubertal Gir heifers and 6 postpartum Gir cattle using an ultrasound. The Gir heifers indicated the presence of 2- follicular wave (n=4) and 3-wave (n=2) estrous cycle. The second wave appeared earlier with 3-wave than with 2-wave (p<0.05). The linear growth rate, persistence and duration of regression phase of first dominant follicle were longer in 2-wave cycle (p<0.05). The maximum diameter of ovulatory follicle (OF) was higher in 3-wave cycle, whereas its linear growth rate was higher in 2-wave cycle (p<0.05). The follicular turnover in postpartum Gir cattle was also characterized by 2- and 3-waves in equal frequency. The linear growth rate and persistence of OF was more and persistence was less in 3-wave cycle (p<0.01). All other parameters of 2- and 3-wave cycle of Gir cattle were similar. The study concluded that 2-wave cycles are more common with slightly shorter cycle length in Gir heifer than the pluriparous Gir cattle.